Effectiveness Analysis of PDAM Tirta Jaya's Water Distribution System in Pamekasan City: Sumber Nyamplong Case Studi: Analisis Efektivitas Sistem Pendistribusian Air PDAM Tirta Jaya Di Kota Pamekasan: Studi Kasus Sumber Nyamplong - Dian Nissa Fitri Budiani; Hafid Syaifullah (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
The clean water distribution system in Pamekasan faces obstacles in the form of distribution imbalance, suboptimal infrastructure, and pipe leaks, especially in the Sumber Nyamplong area, which is one of the main sources. These problems have an impact on customer dissatisfaction and a decrease in the quality of life of the community. This case study aims to provide strategic solutions to improve the effectiveness of clean water distribution in the area. The activity partner is PDAM Tirta Jaya, a BUMD responsible for providing clean water in the Pamekasan area. A quantitative approach was used with a survey of 95 customers. Data analysis used regression analysis to understand the influence of quantity, quality, and continuity factors on customer satisfaction. The results of the study showed that water quality provided the highest level of satisfaction (65.26%), while continuity and quantity were at 42.11% and 40%, respectively. The proposed solutions include remapping the distribution network, improving the infrastructure system to reduce leaks, and providing reserve tanks for areas with high demand, to support the sustainability of PDAM services in the future.